Indeks sporozoit Anopheles spp. (Culicidae: Anophelinae) di daerah endemis malaria di Kecamatan Kokap, Kabupaten Kulon Progo - Andiyatu Andiyatu; R.C. Hidayat Soesilohadi; Niken Satuti Nur Handayani; Sukarti Moeljopawiro (Jurnal Entomologi Indonesia, 2016)
Intervillage variation of malaria endemicity in the same sub-district is probably related to infectivity variation of Anopheles sp. The purpose of this research was to examine the proportion of sporozoite positive species, or species infectivity (SI), and the proportion of sporozoite positive samples, or total sporozoite index (TSI), of a high endemic village (HEV) and a low endemic village (LEV) in the Kokap Sub-District, Kulon Progro District, Central Java. Four Anopheline species were examined - Anopheles vagus Donitz, Anopheles maculatus (Theobald), Anopheles balabacensis Baisan, and Anopheles aconitus Donitz. Anopheles mosquitoes were concurrently collected in the two villages, five times each during October–December 2013, at two-week intervals, using the resting collection method. The mosquito collection was conducted every hour (50 minutes each) at three houses by two collectors each (one inside and one outside), from 18:00 PM to 06:00 AM. Female parous mosquitoes were examined using the Multiplex-PCR method to detect the presence of sporozoites. The examination of 77 DNA samples showed that the SI and TSI of the two villages (49 HEV and 28 LEV) were significantly different: a SI ratio of  66,7% : 33,3% and a TSI ratio of 20,41% : 3,57% (OR = 6,9; CI95% = 0.87 to 57.29; p = 0.021). This finding indicates that a high intensity malaria transmission could occur in the HEV and that a specific vector control measure is necessary.